Pengaruh Gaya Kepemimpinan, Komunikasi, Disiplin Kerja dan Budaya Organisasi terhadap Kepuasan Kerja pada PT. Bintara Tani Nusantara (BTN) - Putri Azizi; Mardhatila Fitri Sopali (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to determine how much influence leadership style, communication, work discipline and culture have on job satisfaction at PT. NCO Tani Nusantara (BTN) West Pasaman. This study consists of four independent variables, namely leadership style, communication, work discipline and organizational culture and one variable of job satisfaction. The analytical method used is path analysis. The method of data collection in this research is to use a questionnaire filled out by respondents, namely employees of PT. NCO Tani Nusantara (BTN) West Pasaman. The results obtained based on the Partial Test (t test) obtained: a) There is a positive and significant influence of leadership style on job satisfaction, b) There is a positive and significant effect of communication on job satisfaction, c) There is a positive and significant effect of work discipline on job satisfaction. , d) There is a positive and significant influence of organizational culture on job satisfaction, e) There is a positive and significant influence of leadership style, communication, work discipline and organizational culture on job satisfaction. Finally, the author suggested to PT. Bintara Tani Nusantara (BTN) Pasaman Barat to be able to improve employee empowerment, leadership style, communication, work discipline and organizational culture